2007
DOI: 10.1007/s10735-007-9125-2
|View full text |Cite
|
Sign up to set email alerts
|

A study on co-localization of FSH and its receptor in rat hippocampus

Abstract: It has been known that GnRH, LH and their receptors exist in hippocampal neurons. However, whether FSH and its receptor also exist in hippocampal neurons remained unknown yet. In situ hybridization, double-labeled immunofluorescence stain and double-labeled immunohistochemistry stain in adjacent sections were used in our research to study the distribution, co-localization of FSH and its receptor and co-localization of FSH and GnRH receptor in rat hippocampus. The result found that pyramidal neurons from CA1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…This probably explains the difficulty in the detection of FSH cells by IHC using heterologus antisera in some species [16, 21]. The expression of β-LH and β-FSH transcripts in the brain of C. dimerus was consistent with their peptide immunoreactivity previously shown in this species [11], other teleost fish [8, 9] and mammals [3, 4]. In the tilapia O. mossambicus, β-FSH and LH subunits were also cloned and partially sequenced in the preoptic nucleus [9].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This probably explains the difficulty in the detection of FSH cells by IHC using heterologus antisera in some species [16, 21]. The expression of β-LH and β-FSH transcripts in the brain of C. dimerus was consistent with their peptide immunoreactivity previously shown in this species [11], other teleost fish [8, 9] and mammals [3, 4]. In the tilapia O. mossambicus, β-FSH and LH subunits were also cloned and partially sequenced in the preoptic nucleus [9].…”
Section: Discussionsupporting
confidence: 71%
“…It was also shown that LH was present in the rat amygdala, septal area, thalamus, caudate nucleus and hippocampus [3]. Recently, a colocalization of FSH and its receptor in the rat hippocampus was demonstrated [4]. …”
Section: Introductionmentioning
confidence: 99%
“…There are complex inter-regulation mechanisms in these hormones. Our previous study found that not only FSH and its receptor but also FSH and GnRH receptor co-located in pyramidal neurons from CA1 to CA4 region and granule neurons in dentate gyrus, which suggested that FSH might regulate the function of hippocampal neurons by ways of paracrine or autocrine and GnRH might regulate the function of FSH positive neurons in hippocampus through GnRH receptor (Chu et al 2008a). It has been known that GnRH, FSH and estrogen exist in hippocampal neurons together with their receptors.…”
Section: Discussionmentioning
confidence: 97%
“…Although brain receptors for FSH were previously thought to be absent [141], they have now been reported to be present in the hippocampus [151], suggesting functional significance. Indeed, as hippocampal neurons are extrapituitary sites of FSH expression [150], FSH is likely to have local autocrine or paracrine roles.…”
Section: Follicle-stimulating Hormone (Fsh)mentioning
confidence: 93%
“…There is a scarcity of reports on the occurrence of extrapituitary follicle-stimulating hormone (FSH), however, FSH Endocrine (2012) 41:19-30 23 protein and its transcripts have been shown to be present in the brain [142], particularly the preoptic area [143], the hypothalamus [150] and the hippocampus [151]. Although brain receptors for FSH were previously thought to be absent [141], they have now been reported to be present in the hippocampus [151], suggesting functional significance.…”
Section: Follicle-stimulating Hormone (Fsh)mentioning
confidence: 99%